System approaches for scaling agroecology: Five dimensions of success - CGIAR Initiative on Agroecology (2024)
In 2022, the CGIAR Agroecology Initiative embarked on a major effort, relying on strong partnerships with local and national organizations, to demonstrate how a systems approach to agroecological transitions can work under highly diverse conditions in eight target countries. The Initiative is organized into a set of interlinked “work packages,” or WPs (listed below), each responsible for addressing a different dimension of the desired agroecological transition pathway in distinct territories referred to as Agroecological Living Landscapes (ALLs): WP1: Transdisciplinary co-creation of innovations in ALLs. WP2: Evidence-based agroecology assessments. WP3: Inclusive business models and financing strategies. WP4: Strengthening the policy and institutional environment. WP5: Understanding and influencing agency and behavior change. Through this approach, the Initiative aimed to delineate a wide array of environmental and institutional settings (the ALLs) in which stakeholders could collectively choose pathways to agroecology transitions and then co-create corresponding agroecological innovations that are suited to the local context. At the same time, the Initiative worked to create the necessary conditions for agroecological innovations to succeed and expand. By generating extensive science-based evidence of this success, the Initiative intends to inform future investment in agroecology transitions at other locations and on a larger scale. Already, it has helped better position the approach globally, while also demonstrating the value of integrating research capacities across the CGIAR and building trust among donors in the effectiveness of the systems approach.